Calcium looping combustion for high-efficiency low-emission power generation - Hanak, Dawid P.; Manovic, Vasilije (Elsevier, 2017)
High-temperature solid looping technologies, such as calcium looping and chemical looping combustion are regarded as emerging CO2 capture technologies with potential to reduce the net efficiency penalties associated with CO2 separation. Importantly, high-temperature operation of these technologies allows utilisation of the high-grade heat for power generation. Building on these emerging technologies, this study intended to establish a new class of high-temperature solid looping combustion technologies for high-efficiency low-emission power generation called calcium looping combustion. Such combustion technology comprises a combustor, as a primary source of heat for indirect heating in a calciner, and a carbonator where CO2 is separated from flue gas leaving the combustor; hence high-grade heat, which can be used for power generation, and a concentrated CO2 stream, which can be either utilised or permanently stored, are generated. The techno-economic performance of calcium looping combustion was comparable to a conventional coal-fired power plant. Depending on whether the concentrated CO2 stream is utilised elsewhere or permanently stored, calcium looping combustion was characterised with a net efficiency gain of 0.7%HHV points or a net efficiency penalty of 2.4%HHV, respectively. Additionally, the cost of CO2 avoided for calcium looping combustion was estimated to be 10.0 €/tCO2 and 33.9 €/tCO2, respectively. Therefore, similarly to chemical looping combustion, calcium looping combustion introduced in this study is a viable high-efficiency low-emission power generation technology that produces a concentrated CO2 stream with no efficiency penalty associated with CO2 separation.
Keywords: Novel power generation system; Coal-fired power plant; Process modelling and simulation; Techno-economic analysis; Calcium looping; Decarbonisation